Analysis of Amed Salt Farming Income in Purwa Kerhti Village, Abang District, Karangasem Regency, Bali - Ni Luh Puji Pratiwi; Gede Mekse Korri Arisena; I Ketut Suamba (Agribusiness Journal, 2022)
This study aims to determine (1) To find out the analysis of amed salt farming in Purwa Kerthi Village, Abang District, Karangasem Regency, Bali Province in 2020 (2) To find out the marketing system of amed salt Bali area in Purwa Kerthi Village, Abang District, Karangasem Regency, Bali Province in 2020. This research was conducted from March to July 2021. The data collection technique used the snowball sampling method with primary and secondary data. The sample used in the study consisted of 29 respondents. The data analysis method in this research is quantitative and qualitative data analysis. The results of the 2020 research in one season show that the total income of Amed Salt farming is Rp 748,182,000 with an average farmer income of Rp 31,174,250, the R/C ratio is 4 which means that the farm is profitable and the profitability of 3.09% indicates that it deserves to be developed. The marketing institutions involved in marketing the Bali area are the MPIG Garam Amed Cooperative (a producer as well as a wholesaler) and retailers. There are two marketing channels that are efficient, channel I produces a farmer's share of 100%, marketing margin and marketing agency of 0. Channel II produces a farmer's share of 61%, marketing margin and marketing agency Rp 22,125 and 39%. Based on the results of this study, it is hoped that the Purwa Kerthi Village will pay more attention to the existence of Amed Salt and expand its marketing reach to national and international levels.